Development of a patient-centred, evidence-based and consensus-based discharge care bundle for patients with acute exacerbation of chronic obstructive pulmonary disease. Issue 1 (30th January 2018) - Ospina, Maria B; Michas, Marta; Deuchar, Lesly; Leigh, Richard; Bhutani, Mohit; Rowe, Brian H; Marciniuk, Darcy; Goodridge, Donna; Dechman, Gail; Bourbeau, Jean; Balter, Meyer; Camp, Pat; et al.
Abstract : Introduction: Hospital and emergency department discharge for patients with chronic obstructive pulmonary disease (COPD) is often poorly organised. We developed a patient-centred, evidence-based and consensus-based discharge care bundle for patients with acute exacerbations of COPD. Methods: A purposeful sample of clinicians and patients were invited to participate in a two-round Delphi study (July–November 2015). In round 1, participants rated on a seven-point Likert scale (1=not at all important; 7=extremely important) the importance of 29 unique COPD care actions. Round 2 comprised items selected from round 1 based on consensus (>80% endorsement for Likert values 5–7). A list of 18 care items from round 2 was discussed in a face-to-face nominal group meeting. Results: Seven care items were included in the COPD discharge bundle based on clinician and patient input: (1) ensure adequate inhaler technique is demonstrated; (2) send discharge summary to family physician and arrange follow-up; (3) optimise and reconcile prescription of respiratory medications; (4) provide a written discharge management plan and assess patient's and caregiver's comprehension of discharge instructions; (5) refer to pulmonary rehabilitation; (6) screen for frailty and comorbidities; and (7) assess smoking status, provide counselling and refer to smoking cessation programme. Conclusion: We present a seven-item, patient-centred, evidence-based and consensus-based discharge bundle for patients with acute exacerbations of COPD. Alignment with clinical practice guidelines and feasibility of local adaptations of the bundle should be explored to facilitate wide applicability and evaluation of the effectiveness of the COPD discharge bundle.